The role of internal audit in reducing administrative and financial corruption: An applied study at the General Tax Authority (Entrepreneurship Journal for Finance and Business, 2020)
The role played by the internal audit in any service establishment or profitability is an important focus in the work of that establishment because it is considered the safety valve and controls the extent of the commitment of the economic unit of the instructions in force in its operational and the extent of its commitment to accounting systems and financial reports, which will reflect on the efficiency and effectiveness of those The economic unit in its stand to try to exploit its work in the administrative and financial corruption, which is one of the serious factors that destroy the work of that establishment internally and externally.In this research, which undermined the role of internal auditing in the process of reducing the administrative and financial corruption in the General Authority for Taxation through the knowledge of the duties assigned to the internal audit and the need to comply with the instructions issued by the General Authority for Taxes because any violation of these instructions may be a door of administrative and financial corruption Which requires that the internal auditor has an important role in standing against any attempt that may be exploited to exercise administrative and financial corruption in his obligation and instructions and to inform the administration of any violation in the tax work .